Lattice-plasmon-induced asymmetric transmission in two-dimensional chiral arrays - Apurv Chaitanya, N.; Butt, Muhammad; Reshef, O.; Boyd, Robert W.; Banzer, Peter; De Leon, Israel (APL Photonics, 2022)
Asymmetric transmission - direction-selective electromagnetic transmission between two ports - is a phenomenon exhibited by two-dimensional chiral systems. The possibility of exploiting this phenomenon in chiral metasurfaces opens exciting possibilities for applications such as optical isolation and routing without external magnetic fields. This work investigates optical asymmetric transmission in chiral plasmonic metasurfaces supporting lattice plasmon modes and unveils its physical origins. We show numerically and experimentally that asymmetric transmission is caused by an unbalanced excitation of such lattice modes by circularly polarized light of opposite handedness. The excitation efficiencies of the lattice modes, and hence, the strength of the asymmetric transmission, are controlled by engineering the in-plane scattering of the individual plasmonic nanoparticles such that the maximum scattering imbalance occurs along one of the in-plane diffraction orders of the metasurface. Furthermore, we show that only the nonzero diffraction orders contribute to this effect. By highlighting the role of the localized plasmon modes supported by the nanoparticle and their radiative coupling to the lattice structure, our study provides a guideline for designing metasurfaces with asymmetric transmission enabled by lattice plasmons.
CRIS-Team Scopus Importer:2022-02-04

Tuning the Optical and Geometrical Properties of Hybrid Carbon Flakes by Fabrication Parameters - Butt, Muhammad; Mamonova, Daria; Manshina, Alina A.; Banzer, Peter; Leuchs, Gerd (Optics InfoBase Conference Papers, 2020)
We investigate the effects of fabrication parameters on the properties of a selfassembled crystalline carbon-metal hybrid. We show that attenuation and geometrical parameters can be tuned, while high birefringence is observed for all studied cases.
CRIS-Team Scopus Importer:2020-11-13